Eventqual: a measure of perceived quality of sporting event spectators - Ferran Calabuig Moreno, Javier Mundina Gómez, Josep Crespo Hervàs (FEADEF, 2010)
The purpose of this study was to develop a scale for measuring the perceived quality of the spectators at sporting events. A consulting expert's method, known as Delphi, was used in order to propose a first version of the scale. This preliminary scale was administered to a small sample and a few items were eliminated after its analysis leaving a smaller scale. This scale was administered to a sample of 2,111 spectators at a mega-sporting event of multi-sport nature. The scale, named EVENTQUAL, showed good levels of reliability and validity. It underwent an exploratory factor analysis which identified four dimensions of perceived quality of sporting event spectators, which are the tangibles, staff, complementary services and accessibility